2022
DOI: 10.1371/journal.pone.0272383
|View full text |Cite
|
Sign up to set email alerts
|

Prioritized and predictive intelligence of things enabled waste management model in smart and sustainable environment

Abstract: Collaborative modelling of the Internet of Things (IoT) with Artificial Intelligence (AI) has merged into the Intelligence of Things concept. This recent trend enables sensors to track required parameters and store accumulated data in cloud storage, which can be further utilized by AI based predictive models for automatic decision making. In a smart and sustainable environment, effective waste management is a concern. Poor regulation of waste in surrounding areas leads to rapid spread of contagious disease ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Specifically, by promoting major technological innovations and transformative applications such as ecological product design, cleaner production processes, utilization of industrial linkages, and coordinated regional waste disposal and utilization, the advancement of science and technology facilitates the reduction of pollutants at the source and supports the efficient recycling and utilization of resources at multiple levels ( 51 ). In addition, real-time monitoring and analysis of air quality, pollution sources, and emissions can be achieved using scientific and technological means such as digital techniques, remote sensing techniques, and artificial intelligence, which provide data support for the formulation of scientific and reasonable environmental standards and policies and improve the accuracy and effectiveness of environmental regulation ( 52 , 53 ). Additionally, these methods contribute to the early identification and punishment of unlawful emissions, thus strengthening environmental regulation, enforcement, and supervision ( 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, by promoting major technological innovations and transformative applications such as ecological product design, cleaner production processes, utilization of industrial linkages, and coordinated regional waste disposal and utilization, the advancement of science and technology facilitates the reduction of pollutants at the source and supports the efficient recycling and utilization of resources at multiple levels ( 51 ). In addition, real-time monitoring and analysis of air quality, pollution sources, and emissions can be achieved using scientific and technological means such as digital techniques, remote sensing techniques, and artificial intelligence, which provide data support for the formulation of scientific and reasonable environmental standards and policies and improve the accuracy and effectiveness of environmental regulation ( 52 , 53 ). Additionally, these methods contribute to the early identification and punishment of unlawful emissions, thus strengthening environmental regulation, enforcement, and supervision ( 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…The future of waste management lies in leveraging these technologies to predict waste generation patterns, optimize collection routes, and enhance the overall security of waste management systems. Mishra et al (2022) present an innovative model that combines the Internet of Things (IoT) with AI to create a predictive waste management system. This system utilizes sensors to monitor waste levels in bins and employs AI algorithms to predict when bins will be full, thereby optimizing collection schedules and routes.…”
Section: Future Trends: Predictive Analytics and Ai In Secure Waste M...mentioning
confidence: 99%
“…The model demonstrates a significant improvement in operational efficiency and resource allocation, reducing the time and effort required for waste collection. Furthermore, the predictive capabilities of this model can enhance the security of waste management systems by preventing overflows and ensuring timely collection, thereby mitigating health risks associated with accumulated waste (Mishra et al, 2022). Allahham et al (2023) explore the application of big data analytics and AI in improving the sustainability of hospital supply chains, which includes waste management.…”
Section: Future Trends: Predictive Analytics and Ai In Secure Waste M...mentioning
confidence: 99%
“…The research in [29][30][31][32][33][34] examines the efficacy of ML algorithms like RF and its variations in selecting Single Nucleotide Polymorphisms (SNPs) for fine-scale genetic population assignment in wildlife conservation. The study, which uses unpublished data for Atlantic salmon and published data for Alaskan Chinook Salmon (ACS), found that ML methods outperformed traditional Fixation Index (FST) rankings in identifying informative genetic markers.…”
Section: Literature Reviewmentioning
confidence: 99%